1993
DOI: 10.1136/jnnp.56.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Miller Fisher syndrome is associated with serum antibodies to GQ1b ganglioside.

Abstract: A recent report described serum antiGQlb ganglioside antibodies in Miller Fisher syndrome (MFS), a clinical variant of Guillain-Barre syndrome (GBS). Four consecutive cases ofMFS all had high titre anti-GQlb antibodies which were absent from all control sera including those of patients with GBS. (i Neurol Neurosurg Psychiatry 1993;56:204-206) Antibodies directed against gangliosides are being increasingly identified in patients with a variety of acute and chronic neuropathies. ' Patients and methods All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(102 citation statements)
references
References 7 publications
3
94
0
4
Order By: Relevance
“…MFS is an acute postinfectious autoimmune neuropathy which may follow Campylobacter jejuni (Cj) infection. MFS bears a strong clinical resemblance to the phenotype seen in the CANOMAD and over 95% of MFS cases have IgG antibodies to epitopes present on GQ1b and GT1a and other NeuAc(␣2-8)NeuAc(␣2-3)Gal configured gangliosides including GD1b, GT1b, and GD3 (53)(54)(55). It has previously been shown that both the anti-GQ1b antibodies in MFS sera and anti-GM1 antibodies in GBS sera react with carbohydrate epitopes on Cj LPS, and the model proposed for the illness is thus one of molecular mimicry in which the humoral immune response to Cj LPS fortuitously cross-reacts with neural ganglioside antigens, thereby inducing the neuropathy (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…MFS is an acute postinfectious autoimmune neuropathy which may follow Campylobacter jejuni (Cj) infection. MFS bears a strong clinical resemblance to the phenotype seen in the CANOMAD and over 95% of MFS cases have IgG antibodies to epitopes present on GQ1b and GT1a and other NeuAc(␣2-8)NeuAc(␣2-3)Gal configured gangliosides including GD1b, GT1b, and GD3 (53)(54)(55). It has previously been shown that both the anti-GQ1b antibodies in MFS sera and anti-GM1 antibodies in GBS sera react with carbohydrate epitopes on Cj LPS, and the model proposed for the illness is thus one of molecular mimicry in which the humoral immune response to Cj LPS fortuitously cross-reacts with neural ganglioside antigens, thereby inducing the neuropathy (7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the most widely recognised is the Miller Fisher syndrome,2 in which serum antibodies to GQlb are found in over 90% of patients. [3][4][5] Anti-GQlb antibodies are also present in patients with Guillain-Barre syndrome who exhibit ophthalmoplegia.6. These clinicoserological studies have led some authors to suggest that anti-GQlb antibodies are a marker for ophthalmoplegia.…”
mentioning
confidence: 99%
“…El SMF, la oftalmoparesia aguda sin ataxia (OA), la encefalitis de Bickerstaff (EB) y el SGB con oftalmoplejía, serían parte del espectro continuo de este síndrome (14). Nuestro paciente tuvo un dosaje negativo de anticuerpo anti-GQ1b, este resultado no descarta la enfermedad, ya que según los datos reportados, el anticuerpo resulta positivo solo en alrededor del 90% de los casos (15,16), además una posible explicación a este resultado negativo, sería una baja concentración de anticuerpos anti-GQ1b al momento de la toma de muestra (tercera semana de enfermedad), los cuales tiene tienen un pico al inicio de la clínica y disminuyen hasta desaparecer en unas 4-5 semanas (17).…”
Section: Rev Neuropsiquiatr 80 (4) 2017unclassified